Utilization of Bengkalis Beach Sand Silica as Raw Material in the Synthesis of Zeolite 4A - Azis, Yelmida; Zahrina, Ida; Fadli, Ahmad; Hazzamy, Muhammad Asyaf (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Zeolite 4A is a porous material that is widely used as an adsorbent, catalyst, membrane, ion exchanger, molecular sieve, etc. As a source of silica in the synthesis of zeolite 4A, silica from natural materials, biomass waste or chemicals has been used. In this research, silica extracted from Bengkalis beach sand (BBS) was used as raw material. The silica content in its oxide form, silicon oxide (SiO2) in BBS reaches 90%. The synthesis of zeolite 4A was carried out using a hydrothermal process, by varying the mole ratio of Si/Al from the reactant sodium silicate to sodium aluminate, namely 1.2:1; 1.4:1; 1.6:1 at reaction temperatures of 100, 110 and 120°C. Based on characterization using X-ray diffraction and an infrared spectrometer, the best conditions were obtained at a mole ratio reactant of 1.6, a reaction temperature of 100°C with a crystallinity percentage reaching 80.97%. Based on SEM-EDX analysis, the zeolite has an agglomerated morphology with a Si/Al ratio of around 1.09. The surface area, pore volume, and pore diameter of the synthesized zeolite were analyzed using a Brunauer-Emmet-Teller (BET) technique, respectively 81.844 m2/g, 0.039 cm3/g, and 3.07 nm.